The nordic hamstring exercise: awareness, implementation and opinion of worldwide athletes - Al Attar, W. S. A.; Akkam, A. M.; Al Hazmi, N. N.; Aljedaani, E. F.; Ghulam, H. S. H.; Dorgham, H. A.; Sanders, R. H. (British Journal of Sports Medicine, 2021)
Background:Soccer has high injury risk, especially for hamstring muscle injuries, and the Nordic hamstring exercise is a well-known intervention to prevent them. Objective: To assess the professional and semi-professional soccer players and coaches' awareness, implementation, and opinion of the Nordic hamstring exercise. Design: A cross-sectional study. Setting An online survey for all continental football federations. Patients (or Participants) A total of 812 male (88.3%) and female (11.7%) professional and semi-professional soccer players and coaches completed the survey. Interventions (or Assessment of Risk Factors) The questionnaire consisted of questions relating to the awareness level, implementation rate, and opinion of the of the Nordic hamstring exercise. Questions development was guided by several authors whose expertise is in sport medicine and injury prevention. Main Outcome Measurements: The primary outcomes were awareness level, implementation rate, and opinion of the effectiveness of the Nordic hamstring exercise in reducing hamstring injury. Results: A total of 395 (48.6%) of professional and semi-professional soccer players and coaches were aware of the Nordic hamstring exercise, 355 (43.7%) were implementing the Nordic hamstring exercise in their current practice. Participants who implemented the Nordic hamstring exercise reported a positive opinion about the program efficacy, with a score of 8.6±1 out of 10. Conclusions: Further work needs to be done to educate soccer players and coaches about the importance of implementing the Nordic hamstring exercise and its effectiveness in preventing hamstring injury to enhance implementation of the Nordic hamstring exercise.